Isolation and characterization of A2-EPTX-Nsm1a, a secretory phospholipase A2 from Malaysian spitting cobra (naja sumatrana) venom - Abdullah, Nur Atiqah Haizum; Ahmad Rusmili, Muhamad Rusdi; Zainal Abidin, Syafiq Asnawi; Shaikh, Mohd Farooq; C. Hodgson, Wayne; Othman, Iekhsan (MDPI, 2021)
Phospholipase A2 (PLA2) toxins are one of the main toxin families found in snake venom. PLA2 toxins are associated with various detrimental effects, including neurotoxicity, myotoxicity,hemostatic disturbances, nephrotoxicity, edema, and inflammation. Although Naja sumatrana venom contains substantial quantities of PLA2 components, there is limited information on the function and activities of PLA2 toxins from the venom. In this study, a secretory PLA2 from the venom of Malaysian N. sumatrana, subsequently named A2-EPTX-Nsm1a, was isolated, purified, and characterized. A2-EPTX-Nsm1a was purified using a mass spectrometry guided approach and multiple chromatography steps. Based on LC-MSMS, A2-EPTX-Nsm1a was found to show high sequence similarity with PLA2 from venoms of other Naja species. The PLA2 activity of A2-EPTX-Nsm1 was inhibited by 4-BPB and EDTA. A2-EPTX-Nsm1a was significantly less cytotoxic in a neuroblastoma cell line (SH-SY5Y) compared to crude venom and did not show a concentration-dependent cytotoxic activity. To our knowledge, this is the first study that characterizes and investigates the cytotoxicity of an Asp49 PLA2 isolated from Malaysian N. sumatrana venom in a human neuroblastoma cell line.